A Digital Voice for Russian Rock: Perspectives on Digitization of Russian Rock Zines. (3rd April 2019) - Trotter, Veronika
ABSTRACT: Soviet and post-Soviet rock music zines comprise a fascinating resource not only for historians of music, but also for cultural historians, graphic designers, linguists, and specialists in other disciplines as well as the general public. This article discusses the importance of creating a digital project, based on the highly unique Russian rock/Youth Counterculture rock zine collection from the Global Resources Center at the George Washington University Library and other sources. The author describes the content and organization of the project, which would serve as a platform for research and teaching. In addition, various challenges involved in the implementation of the project, such as copyright issues, are addressed.